Preservation of Traditional Art in Batur Traditional Village through Training In The Gamelan Angklung Don Pitu | Pelestarian Seni Tradisi Di Desa Adat Batur Melalui Pelatihan Gamelan Angklung Don Pitu - I Nengah Sama (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Batur Village is located in the highlands in Kintamani District, Bangli Regency. Batur Traditional Village has three village areas, namely North Batur Village, Central Batur Village and South Batur Village, now known as Batur Traditional Village. Batur Traditional Village is very famous in the arts field, a characteristic of Batur Traditional Village, namely gamelan gong gede and line dance. The reason why the author conducts Thematic KKN in Batur Village is because of a letter from the Dean of the Faculty of Performing Arts in response to a letter from the Batur Traditional Village requesting support for the Preservation of Traditional Arts in Batur Traditional Village to ISI Denpasar. In Batur Village, two gamelan barungan need guidance from students, namely Semara Pegulingan gamelan and Angklung don pitu gamelan. The work program to be implemented in this Thematic KKN focuses on kara witan art by conducting training on existing tabuh-tabuh and also creating a new tabuh work on gamelan angklung don pitu entitled